Cover image. Issue 2 (24th October 2022) - Zhang, Yijian; Hou, Mingzhuang; Liu, Yang; Liu, Tao; Chen, Xi; Shi, Qin; Geng, Dechun; Yang, Huilin; He, Fan; Zhu, Xuesong
Abstract : The cover image is based on the Original Article Recharge of chondrocyte mitochondria by sustained release of melatonin protects cartilage matrix homeostasis in osteoarthritis by Yijian Zhang et al., https://doi.org/10.1111/jpi.12815 .